Assessment of mid-upper arm circumference for detecting obesity in pregnant women: a cross-sectional study - Ali, Moayad H.; AlHabardi, Nadiah; Adam, Ishag (Frontiers in Global Women's Health, 2025)
IntroductionLimited studies have assessed the accuracy of mid-upper arm circumference (MUAC) in diagnosing nutritional status among pregnant women in Sub-Saharan Africa, and none in Rwanda. This study aimed to evaluate the effectiveness of MUAC in detecting obesity among pregnant women at Kacyiru Hospital in Kigali, Rwanda.MethodsThis cross-sectional study was conducted at Kacyiru Hospital, a district hospital in Kigali, Rwanda. Standard procedures were used to measure MUAC, weight, and height, from which body mass index (BMI) was calculated. Receiver operating characteristic (ROC) curves were created to determine cutoff points using Youden's index (YI).ResultsA total of 689 women were enrolled. The median (interquartile range) age and gravidity were 29.0 (26.0–33.0) years and 2 (1–3), respectively. Among the 592 women (85.9%) with gestational ages of ≥20.0 weeks, 5 (0.7%) were underweight and 195 (28.3%) were obese. There was a significant correlation between BMI and MUAC (r = 0.78) across all women and within the early (r = 0.774) and late pregnancy subgroups. The optimal MUAC cutoff for detecting obesity (BMI ≥ 30.0 kg/m²) was ≥27.5 cm in both early and late pregnancies (YI = 0.58, sensitivity = 0.91, specificity = 0.67), with a high predictive value [area under the receiver operating characteristic curve (AUROCC) = 0.88, 95% confidence interval (CI) = 0.85–0.90]. In early pregnancy, the best MUAC cutoff was ≥29.5 cm (YI = 0.73, sensitivity = 0.92, specificity = 0.80), with a high predictive value (AUROCC = 0.87, 95% CI = 0.77–0.97). In late pregnancy, the best MUAC cutoff was ≥27.5 cm (YI = 0.62, sensitivity = 0.92, specificity = 0.71), with a high predictive value (AUROCC = 0.89, 95% CI = 0.87–0.92).ConclusionMUAC is a reliable indicator for detecting obesity in pregnant women. Further research with larger sample sizes and follow-up studies is needed to assess MUAC's ability to detect underweight status and related adverse pregnancy effects.